Systematic review: probiotics in the management of lower gastrointestinal symptoms - an updated evidence-based international consensus - Hungin, A P S; Mitchell, C R; Whorwell, P; Mulligan, C; Cole, O; Agréus, L; Fracasso, P; Lionis, C; Mendive, J; Philippart de Foy, J-M; Seifert, B; Wensaas, K-A; et al. (Alimentary pharmacology & therapeutics, 2018)
BACKGROUND: In 2013, a systematic review and Delphi consensus reported that specific probiotics can benefit adult patients with irritable bowel syndrome (IBS) and other gastrointestinal (GI) problems. AIM: To update the consensus with new evidence. METHODS: A systematic review identified randomised, placebo-controlled trials published between January 2012 and June 2017. Evidence was graded, previously developed statements were reassessed by an 8-expert panel, and agreement was reached via Delphi consensus. RESULTS: A total of 70 studies were included (IBS, 34; diarrhoea associated with antibiotics, 13; diarrhoea associated with Helicobacter pylori eradication therapy, 7; other conditions, 16). Of 15 studies that examined global IBS symptoms as a primary endpoint, 8 reported significant benefits of probiotics vs placebo. Consensus statements with 100% agreement and "high" evidence level indicated that specific probiotics help reduce overall symptom burden and abdominal pain in some patients with IBS and duration/intensity of diarrhoea in patients prescribed antibiotics or H. pylori eradication therapy, and have favourable safety. Statements with 70%-100% agreement and "moderate" evidence indicated that, in some patients with IBS, specific probiotics help reduce bloating/distension and improve bowel movement frequency/consistency. CONCLUSIONS: This updated review indicates that specific probiotics are beneficial in certain lower GI problems, although many of the new publications did not report benefits of probiotics, possibly due to inclusion of new, less efficacious preparations. Specific probiotics can relieve lower GI symptoms in IBS, prevent diarrhoea associated with antibiotics and H. pylori eradication therapy, and show favourable safety. This study will help clinicians recommend/prescribe probiotics for specific symptoms.
Keywords: průjem; probiotika; syndrom dráždivého tračníku; konsensus; Diarrhea; Probiotics; Animals; Consensus; Humans; Helicobacter Infections; Helicobacter pylori; lidé; Irritable Bowel Syndrome; Randomized Controlled Trials as Topic; zvířata; infekce vyvolané Helicobacter pylori; randomizované kontrolované studie jako téma